»There's life in the old dog yet« – A Plea for Historical Materialism (KULT_online, 2012)
With the German translation of Democracy against Capitalism: Renewing Historical Materialism, New ISP has released a book onto the German market which rebels against the spirit of the times. Fifteen years after their publication in English, this collection of articles by Marxist author Ellen Meiksins Wood is aimed at a fertilization of the debate on the characteristics of capitalism and the principles of historical materialism between advocates and opponents of Marxism as well as among members of the sociopolitical Left. The volume is a criticism of the current circumstances and the bourgeois, but also of the Marxist historiography; it is not, however, an overview of or an introduction to historical materialism. Even though "renewing historical materialism" undoubtedly requires further publications, this one surely contributes to the discussion.